The influence of desensitizing dentifrices on pain induced by in-office bleaching - Carlos Henrique Thiesen; Rubens Rodrigues Filho; Luiz Henrique Maykot Prates; Neimar Sartori (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The purpose of this study was to evaluate whether the use of desensitizing dentifrices used 15 days prior to and after in-office tooth bleaching could eliminate or reduce tooth sensitivity. After institutional review board approval and informed consent, 45 subjects were selected and divided into 3 groups according to the dentifrice selected: Colgate Total (CT), Colgate Sensitive Pro-Relief (CS) or Sensodyne ProNamel (SP). The subjects used toothpaste and a toothbrush provided to them for 15 days prior to bleaching. They were then submitted to two in-office bleaching sessions (Whiteness HP Blue Calcium). Their tooth sensitivity was assessed using the Visual Analog Scale (VAS) for a week after each session. Their tooth shade alteration was measured with a Vitapan Classical shade guide to determine if the dentifrices could influence the effectiveness of the bleaching agent. The data were submitted to Wilcoxon, Kruskal-Wallis and Mann-Whitney tests (α = 0.05). The use of desensitizing dentifrices did not affect the bleaching efficacy. In regard to tooth sensitivity, there was a statistically significant difference between the results of the Control Group and Group T2 after the first session (p = 0.048). There was no statistically significant difference in the results for the other groups after the first session. In regard to the second session, there was no statistically significant difference in the results for all the groups. The use of a desensitizing dentifrice containing nitrate potassium reduced tooth sensitivity during the bleaching regimen. Dentifrices containing arginine and calcium carbonate did not reduce tooth sensitivity. Color change was not influenced by the dentifrices used